2019
DOI: 10.3390/pr7100757
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and Kinetic Studies of Biosorptive Removal of 2,4,6-Trichlorophenol from Aqueous Solutions Using Untreated Agro-Waste Pine Cone Biomass

Abstract: The present work discusses the adsorptive removal of a phenolic pollutant, i.e., 2,4,6-trichlorophenol (TCP), using low cost untreated agricultural waste pine cone powder (PCP). The present biosorbent was thoroughly characterized with the help of FTIR, SEM, XRD, and CHN analysis. The presence of amine (-NH 2 ), hydroxyl (-OH) and carbonyl (C=O) functional groups was detected by the FTIR analysis. The important biosorption factors like agitation time, biomass dosage, initial adsorbate concentration, and the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 55 publications
2
8
0
1
Order By: Relevance
“…The variation in the removal efficiency e s tablished that CiL-plant is tolerant in a solution of PCP, compared to TCP. This observation agrees with previous research works reported in the literature [8,30] and confirms the optimization report in section 3.1. The synergetic effect of initial concentration*contact time is illu s trated in the outline the contour plot in Figure 8 (c,d).…”
Section: Synergetic Impact Of Time-ph and Concentration-ph On The Bio...supporting
confidence: 94%
See 3 more Smart Citations
“…The variation in the removal efficiency e s tablished that CiL-plant is tolerant in a solution of PCP, compared to TCP. This observation agrees with previous research works reported in the literature [8,30] and confirms the optimization report in section 3.1. The synergetic effect of initial concentration*contact time is illu s trated in the outline the contour plot in Figure 8 (c,d).…”
Section: Synergetic Impact Of Time-ph and Concentration-ph On The Bio...supporting
confidence: 94%
“…The output reduces efficiency from 75% to 63% for PCP and <65% for TCP, as indicated by the curvature of the blue contour gradient in Figure 8 (c,d) and corresponding 3D surfaces in Figure 3. This outcome indicates that the initial concentration has a ceiling effect on the driving force of CiLplant biosorption of PCP and TCP [30,31]. In contra s t, the contact time or exposure had a significant main effect on the phytoremediation process.…”
Section: Synergetic Impact Of Time-ph and Concentration-ph On The Bio...mentioning
confidence: 87%
See 2 more Smart Citations
“…Естественным регулятором этого процесса является степень диссоциации карбоксильных групп, которая, с одной стороны, определяет количество реакционноспособных группировок, а с другой стороны, влияет на плотность гидратной оболочки вокруг полимерной цепи. В связи с этим оптимум кислотности в процессах связывания катионных сорбатов у разных исследователей [78][79][80][81][82][83] сильно варьирует в зависимости от плотности заряда на поверхности сорбируемой частицы и вида пектинового субстрата.…”
Section: рис 2 ик-спектры пропускания препаратов пектиновых веществ из льняных субстратов: 1 -P Migr ; 2 -P Bast ; 3 -P Par ; 4 -P Xylunclassified